DESAIN JARINGAN DISTRIBUSI BERBASIS E-BUSINESS PADA SISTEM RANTAI PASOK - Fino Wahyudi Abdul; Yuli Evitha (Institut Ilmu Sosial dan Manajemen Stiami, 2019)
In this paper, we provide a form of distribution network design and application in the field of e-commerce in the supply chain, with a distribution network design approach. Thus a good distribution network model can be determined in e-commerce business and provide quality service through the delivery period of equipment and materials to the consumer's location that is fast and low cost which can provide more competitive prices for customers. This is where the role of distribution is very important, because with the distribution of all materials both raw materials and finished products can be distributed to each party in need in the supply chain. In the supply chain itself there are several distribution designs available, namely Manufacturer Storage With Direct Shipping, Manufacturer of Storage with Direct Shipping and In-Transit Merge, Storage With Carrier Delivery Distributor, Storage With Last-Mile Delivery Distributor, Manufacturer Or Distributor Storage With Customer Pickup.